Difficulty scoring system in laparoscopic distal pancreatectomy. (17th September 2018) - Ohtsuka, Takao; Ban, Daisuke; Nakamura, Yoshiharu; Nagakawa, Yuichi; Tanabe, Minoru; Gotoh, Yoshitaka; Velasquez, Vittoria Vanessa D. M.; Nakata, Kohei; Sahara, Yatsuka; Takaori, Kyoichi; Honda, Goro; Misawa, Takeyuki; et al.
Abstract: Background: Several factors affect the level of difficulty of laparoscopic distal pancreatectomy (LDP). The purpose of this study was to develop a difficulty scoring (DS) system to quantify the degree of difficulty in LDP. Methods: We collected clinical data for 80 patients who underwent LDP. A 10‐level difficulty index was developed and subcategorized into a three‐level difficulty index; 1–3 as low, 4–6 as intermediate, and 7–10 as high index. The automatic linear modeling (LINEAR) statistical tool was used to identify factors that significantly increase level of difficulty in LDP. Results: The operator's 10‐level DS concordance between the 10‐level DS by the reviewers, LINEAR index DS, and clinical index DS systems were analyzed, and the weighted Cohen's kappa statistic were at 0.869, 0.729, and 0.648, respectively, showing good to excellent inter‐rater agreement. We identified five factors significantly affecting level of difficulty in LDP; type of operation, resection line, proximity of tumor to major vessel, tumor extension to peripancreatic tissue, and left‐sided portal hypertension/splenomegaly. Conclusions: This novel DS for LDP adequately quantified the degree of difficulty, and can be useful for selecting patients for LDP, in conjunction with fitness for surgery and prognosis. Abstract : Highlight Ohtsuka and colleagues set out to develop a difficulty scoring system for laparoscopic distal pancreatectomy. This novel system adequately quantifies the degree of difficulty, and can be useful for selecting patients for laparoscopic distal pancreatectomy and for aiding surgeons wishing to learn or teach this procedure in a stepwise manner.